Metode dan Strategi Guru PAI dalam Penanaman Nilai-Nilai Pendidikan Karakter (Studi Kasus di SMPN 6 Taman Kabupaten Pemalang) - Prayogi, Arditya; Fina Firqotun Najiyah (Indonesian Journal Publisher, 2023)
This article was written with the aim of describing the strategies used by Islamic religious education teachers at SMP Negeri 6 Taman, Pemalang Regency in instilling character education values. Apart from that, various supporting and inhibiting factors are also described in instilling character education values for class VIII students at SMP Negeri 6 Taman, Pemalang Regency. This is because character development is an important thing that must be done by teachers, especially Islamic religious education (PAI) teachers. This is because through religious education (Islam), teachers can introduce students to and at the same time instill social values that live and are maintained in people's lives which are part of good human character and personality. This article uses a type of field research by applying a qualitative approach. Data collection techniques are carried out through observation, interviews and documentation. Meanwhile, the data analysis technique goes through three stages, namely data reduction, data presentation process, and conclusion drawing process. The results of the study in this article show that the PAI teacher's strategy in instilling character education values in class VIII students at SMP Negeri 6 Taman, Pemalang Regency uses several strategies, namely through habituation activities, being a model and role model, mentor and motivator, and giving punishment. The supporting factors in instilling character education values in students are teachers who can be role models, parental education at home, school facilities, routine and extracurricular school activities. Meanwhile, the inhibiting factors are lack of teacher competence, lack of parental education, environmental and social factors.